2017
DOI: 10.1038/ng.3889
|View full text |Cite|
|
Sign up to set email alerts
|

DNMT and HDAC inhibitors induce cryptic transcription start sites encoded in long terminal repeats

Abstract: Several mechanisms of action have been proposed for DNA methyltransferase and histone deacetylase inhibitors (DNMTi and HDACi); mainly based on candidate gene approaches. However, less is known about their genome-wide transcriptional and epigenomic consequences. By mapping global transcription start site (TSS) and chromatin dynamics, we observed the cryptic transcription of thousands of treatment-induced non-annotated TSSs (TINATs) following DNMTi and/or HDACi treatment. The resulting transcripts frequently sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
227
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(268 citation statements)
references
References 70 publications
29
227
1
1
Order By: Relevance
“…We noted that PASs often locate to intergenic regions with homology to transposable elements (TEs). In humans, it is common to find nonannotated transcription start sites (TSS) in their long terminal repeats (LTRs) modulated by epigenetic mechanisms (Brocks et al ., ). In our experiments, this type of epigenetic regulation can be responsible for the distinct expression of orphan PASs observed in M. oryzae TEs under different nutritional conditions.…”
Section: Discussionmentioning
confidence: 97%
“…We noted that PASs often locate to intergenic regions with homology to transposable elements (TEs). In humans, it is common to find nonannotated transcription start sites (TSS) in their long terminal repeats (LTRs) modulated by epigenetic mechanisms (Brocks et al ., ). In our experiments, this type of epigenetic regulation can be responsible for the distinct expression of orphan PASs observed in M. oryzae TEs under different nutritional conditions.…”
Section: Discussionmentioning
confidence: 97%
“…DNase hypersensitivity is associated with both active gene promoters and distal enhancers. LTR12C elements, for example, were previously shown to frequently act as alternative gene promoters in different cell types, including hepatocellular carcinoma (Hashimoto et al, 2015) and cell lines treated with DNMT and HDAC inhibitors (Brocks et al, 2017). In contrast, LTR5_Hs (HERV-K) elements appear to mainly act as distal enhancer elements in embryonic carcinoma cells and embryonic stem cells (Fuentes et al, 2018;Pontis et al, 2019).…”
Section: A-dars Bear Signatures Of Enhancer Elementsmentioning
confidence: 99%
“…In addition, it has been reported that treatment of epithelial cancer cell lines (including CRC cells) with demethylating agents, namely 5-azacitidine, leads to a significant enrichment of immunomodulatory pathways (interferon signaling, antigen processing and presentation, and cytokines/chemokines) (97). Lately, Brocks et al (98) demonstrated the genome-wide transcriptional and epigenomic consequences of DNA methyltransferases inhibitors (DNMTi) and histone deacetylase inhibitors (HDACi): cryptic transcription of thousands of treatment-induced non-annotated transcriptional start sites (TINATs) may contribute to cancer immunogenicity due to novel translated potential antigenic proteins.…”
Section: Clinical Implications For Crc Patients and Future Directionsmentioning
confidence: 99%